Exotic species, rather than low flow, negatively affect native fish in the Oglio River, Northern Italy. (23rd July 2018) - Gavioli, Anna; Mancini, Marco; Milardi, Marco; Aschonitis, Vassilis; Racchetti, Erica; Viaroli, Pierluigi; Castaldelli, Giuseppe
Abstract: Rivers worldwide are impacted by human activities such as habitat degradation, habitat fragmentation, waterway flow regulation, and introduction of exotic species, which are responsible for the reduction or the disappearance of native species in many parts of the world. The Oglio River, a tributary of the Po River in Northern Italy, is a good example of a river with a long history of human alteration and where exotic invasions are present. We used data on water parameters and fish communities along the watercourse to investigate whether low flow conditions, degraded water quality, abundant exotic species, and the presence of migration barriers could be a disadvantage for native species. We used ordination methods (redundancy analysis), variance partitioning analysis, and the threshold indicator taxa analysis to explore changes in community composition and ecofunctional traits along an altitude gradient. We found that exotic species affected native ones more than water quality and hydromorphological parameters. Native species were most abundant in the upper reach of the Oglio River, despite low flow and shallow depth. Moreover, rheophilic and clear water native fish decreased rapidly in the lower reach of the river, where exotic species increased. This distribution could be explained by the presence of barriers in the middle reach, which block exotic species migrating upstream from the highly invaded Po River, and by a lower suitability of the upper reach for some exotic species. Our results provide a general description of the fish fauna of a strongly regulated river and can contribute to develop more effective fish and water management practices.